SITE IDENTIFICATION FOR RECESSIONAL IRRAGATION FARMING AROUND DADIN KOWA DAM GOMBE STATE, NIGERIA - Jibril, B. A.; Adamu, M. A.; John, D. M.; Ismail, A. A.; Isa, W. A. (FUDMA JOURNAL OF SCIENCES, 2023)
The use of floodwater for agricultural purposes is practiced worldwide. Mostly on small-scale, farmers practice methods to cope with the annually occurring floods and use them for their benefits. This study is aimed at identifying suitable site(s) for floods recessional farming around Dadin kowa dam. Two dataset of Santinel-2A of 2017 and soil data were analyzed using band ratio and overlay analysis techniques. The finding of this research shows that the total flood recessional area covers 107.037 km2. Upon which 25.32% attributed to very low suitable class, 4.13% belongs to low suitable region, 39.75% goes to moderate suitable area and high suitable zone takes the proportion of 30.80% of the total recessional area. The finding shows that there is appreciable suitable land for recessional farming around Dadin kowa dam. Finally, it is recommended that State Agricultural Development Project should introduced and directed the identified sites to local farmers, so as to improve socio-economic well-being of the farmer